Economic Contributions of Agriculture, Natural Resources, and Related Industries in Florida for 2010 - Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
Agriculture, natural resources, and related industries remain a significant force in the economy of Florida, and it is important to recognize their economic contributions for informed public policy. The economic contributions of these industries were evaluated for 2010 to update previous reports and provide further information on economic trends in the wake of the historic global recession of 2007–2009. This 27-page report was written by Alan W. Hodges, Mohammad Rahmani, and Thomas J. Stevens, and published by the UF Department of Food and Resource Economics, August 2012.